Heuristic Methods for Delay Constrained Least Cost Routing Using$k$-Shortest-Paths - Jia, Z.; Varaiya, P. (IEEE transactions on automatic control, 2006)
The delay constrained least cost (DCLC) problem is to find the least cost path in a graph subject to a delay constraint. First formulated in the context of routing in computer networks, the DCLC model also applies to problems of path planning and other decision problems. DCLC isNP-complete. Many heuristic methods have been proposed for it. This note presents two new methods based on thek-shortest-path(k SP)approach. These heuristic methods - one centralized, the other distributed - are both polynomial. In numerical experiments the proposed algorithms almost always find the optimal paths.